Unlocking the value of real-time analytics : how to architect a real-time data infrastructure - Gardner, Christopher (O'Reilly Media, Inc., 2023)
Storing data and making it accessible for real-time analysis is a huge challenge for organizations today. In 2020 alone, 64.2 billion GB of data was created or replicated, and it continues to grow. With this report, data engineers, architects, and software engineers will learn how to do deep analysis and automate business decisions while keeping your analytical capabilities timely. Author Christopher Gardner takes you through current practices for extracting data for analysis and uncovers the opportunities and benefits of making that data extraction and analysis continuous. By the end of this report, you’ll know how to use new and innovative tools against your data to make real-time decisions. And you’ll understand how to examine the impact of real-time analytics on your business. Fast and fresh data can make the difference between a successful transaction and a missed opportunity. The report shows you how.